2013
DOI: 10.5194/bgd-10-14887-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcium carbonate corrosivity in an Alaskan inland sea

Abstract: Ocean acidification is the hydrogen ion increase caused by the oceanic uptake of anthropogenic CO2, and is a focal point in marine biogeochemistry, in part, because this chemical reaction reduces calcium carbonate (CaCO3) saturation states (Ω) to levels that are corrosive (i.e. Ω ≤ 1) to shell-forming marine organisms. However, other processes can drive CaCO3 corrosivity; specifically, the addition of tidewater glacial melt. Carbonate system data collected in Ma… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 69 publications
3
36
0
Order By: Relevance
“…Similar results of decreased pH and Ω due to the effect of glacial drainage water were found in the sub‐Arctic inland sea of the Prince William Sound in Alaska by Evans et al . [].…”
Section: Resultsmentioning
confidence: 99%
“…Similar results of decreased pH and Ω due to the effect of glacial drainage water were found in the sub‐Arctic inland sea of the Prince William Sound in Alaska by Evans et al . [].…”
Section: Resultsmentioning
confidence: 99%
“…The acceleration of glacial retreat ensures that this freshwater source will play a continually larger role in the freshwater flux and carbonate saturation state of the Arctic and subarctic seas in the near future. As regions where glaciers flow into the ocean, Arctic and subarctic fjords are particularly susceptible to increases in both air and seawater temperatures (Hop et al, 2002;Cottier et al, 2005) that melt ice and thereby influence the carbon cycle through impacts on the saturation state of calcium carbonate (Brown, 2002;Sejr et al, 2011;Rysgaard et al, 2012), primary production (Wiktor, 1999;Zajaczkowski, et al, 2010), and the uptake of atmospheric carbon dioxide (Evans et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent field observations (Evans et al, ) have shown that the inner and middle shelf of the GOA currently experiences seasonal manifestations of corrosive events (Ω < 1), including decreased pH and suppressed Ω in response to rising CO 2 levels and increased discharge of low‐alkalinity, glacial meltwater (Evans et al, ; Reisdorph & Mathis, ). While the glacial discharge mainly influences water on the inner shelf, upwelling brings nutrient and CO 2 ‐rich waters that are undersaturated in the calcium carbonate mineral aragonite from the deep GOA onto the outer shelf (Evans et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A portion of the ACC flows through Prince William Sound (Figure ; Niebauer et al, ; Royer et al, ; Vaughan et al, ) and, thus affects the heat, salt, nutrient, and carbon budgets of the sound and its adjacent bays (Gay & Vaughan, ). This narrow (∼40 km), swift, year‐round flow is maintained by the integrated forcing of winds and freshwater discharge with seasonally high rates of glacier runoff (Evans et al, ). Both the winds and the discharge vary seasonally, although not in‐phase with one another: discharge is a maximum in fall and the westward (downwelling‐favorable) winds are strongest in winter.…”
Section: Introductionmentioning
confidence: 99%